Agricultural Communications: A National Portrait of Undergraduate Courses - Karen J. Cannon; Annie R. Specht; Emily B. Buck (Journal of Applied Communications, 2016)
Considerable research has been conducted regarding competencies needed by agricultural communication program graduates during the past four decades. However, no studies have considered actual program offerings. This study used a qualitative approach to analyze courses offered in agricultural communication programs in the United States. Using content analysis methods, researchers analyzed published course descriptions and discovered 21 categories among 172 courses. Most popular were writing courses, followed by courses introducing students to the major, internship courses, and writing for publication and graphic design courses. Categories with the fewest offerings included research, study abroad, and international focused courses. Findings from this analysis are consistent with previous literature noting the variety existing in agricultural communication programs at the national level. With the current growth of agricultural communication as an academic discipline and the fundamental role agricultural communicators play in sharing information about key societal issues at a time when agriculture has never been under greater pressure, this study is a first step in creating a national portrait of curricular offerings in agricultural communication programs.
Keywords: Agricultural Communications; Curriculum; Content Analysis; Course Descriptions; Qualitative Methods